Static Regime Imaging of Locations of Certain 3D Electromagnetic Imperfections from a Boundary Perturbation Formula (Journal of Computational Mathematics, 2018)
We are concerned, in a static regime, with an imaging approach of the locations in a three-dimensional bounded domain of certain electromagnetic imperfections. This approach is related to Electrical Impedance Tomography and makes use of a new perturbation formula in the electric fields. We present two localization procedures, from a Current Projection method that deals with the single imperfection context and an inverse Fourier process that is devoted to multiple imperfections configurations. These procedures extend those that were described in our previous work, since operating for a broader class of settings. Namely, the localization is additionally performed for certain purely electric imperfections, as established from numerical simulations.